1998
DOI: 10.1143/jjap.37.l462
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Selective Chemical Vapor Deposition of Copper by Nitrogen Plasma Pretreatment

Abstract: Selective chemical vapor deposition of copper on TiN in the presence of borophosphosilicate glass (BPSG) was achieved by RF N2 plasma pretreatment. Without N2 plasma pretreatment, the copper films deposited on BPSG as well as TiN at the deposition temperature of 170°C, while N2 plasma treatment prior to copper deposition led to the significant suppression of the copper nucleation on BPSG. As the plasma pretreatment temperature was increased, the suppression of the copper nucleation on BPSG was increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…However, nonselective deposition and poor film conformity are the disadvantages of plasma-assisted CVD . Also, the plasma can cause damage to the underlying substrate . Laser-assisted CVD is potentially useful for direct-write applications; a laser is used to heat a substrate, inducing pyrolysis of the Cu precursor …”
Section: Cu Mocvd Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, nonselective deposition and poor film conformity are the disadvantages of plasma-assisted CVD . Also, the plasma can cause damage to the underlying substrate . Laser-assisted CVD is potentially useful for direct-write applications; a laser is used to heat a substrate, inducing pyrolysis of the Cu precursor …”
Section: Cu Mocvd Techniquesmentioning
confidence: 99%
“…Some precursors will selectively deposit Cu on conductive surfaces such as metals but not on dielectric surfaces, for example, SiO 2 . Examples of this are (hfac)Cu(COD), which deposits indiscriminately on both tungsten and SiO 2 surfaces, whereas (hfac)Cu(VTMS) can selectively deposit on tungsten in the temperature range 120−420 °C. , Selectivity is clearly determined by the nature of the ligands which surround the metal, and it can also be achieved by exploiting the fact that dielectric surfaces require a higher deposition temperature than conductive materials. , Therefore, by carefully controlling the substrate temperature, Cu can be deposited selectively on conducting materials …”
Section: Precursor Reactivitymentioning
confidence: 99%
“…It was assumed that it is this step that determines the overall process selectivity. 387 Hence, the simplest solution for the selectivity problem can involve suppressing the nucleation 396 or providing conditions where adsorption of molecules of the CCC on the dielectric surface is suppressed, while that on the metal surface is not suppressed. However, this solution also involves certain difficulties.…”
Section: Deposition Of Copper Films In `Metal ± Dielectric' Systemsmentioning
confidence: 99%
“…The Cu films have been deposited by plating, 6,7 sputtering, 8,9 and metallorganic chemical vapor deposition (MOCVD) techniques. [10][11][12][13][14][15][16][17] In the electroplating techniques, the Cu seed layer is needed on barrier metals and is deposited by sputtering technique. 8 As for the MOCVD technique, copper hexafluoroacetylacetonate vinyltrimethylsilane [(C 5 HF 6 O 2 )Cuи(CH 3 ) 3 Si-CHϭCH 2 , Cu 1ϩ (hfac)(vtms)] has been mainly used as the Cu 1ϩ precursor.…”
mentioning
confidence: 99%
“…8 As for the MOCVD technique, copper hexafluoroacetylacetonate vinyltrimethylsilane [(C 5 HF 6 O 2 )Cuи(CH 3 ) 3 Si-CHϭCH 2 , Cu 1ϩ (hfac)(vtms)] has been mainly used as the Cu 1ϩ precursor. [10][11][12][13][14][15][16] The Cu films have been deposited at the substrate temperatures ranging from 130 to 250ЊC. Misawa et al have revealed that the resistivity of Cu films deposited at 200ЊC was 2.05 ⍀-cm, and it decreased to 1.98 and 1.88 ⍀-cm by annealing at 300 and 500ЊC, respectively.…”
mentioning
confidence: 99%